“A Life on Standby”. The Effects of Irregular Status and the Pursuit of Regularity on the Quality of Life of Unaccompanied Minors in Spain - Sajir, Zakaria; Ruiz Andrés, Rafael; Molinero-Gerbeau, Yoan (Calitatea Vieții, 2022)
This article aims at discussing the intersections between unaccompanied migrant minors' (UAM) irregular status and its consequences for their quality of life by focusing on the Spanish context. The research is based on the data collected during a qualitative fieldwork conducted by the authors in a specific reception centre, Sant Joan de Déu-Terres de Lleida, in the province of Lleida (Catalonia) that consisted of 12 in-depth interviews with UAMs, two focus groups with autochthonous and migrant minors and nine in-depth interviews with key actors such as social educators and psychologists. The study shows how the legal status and the social condition of these minors directly affect their future expectations and their integration into the host society. The results indicate that, although they migrated in search for a better life, the process of institutionalisation of which they are part along with the quest for legal documentation lead them to live a life on “standby” where their hopes and dreams are indefinitely postponed, generating a breach with their autochthonous counterparts, which ultimately affects their quality of life in the short and long term.